The Presence of a CMV Immunodominant Allele in the Recipient Is Associated With Increased Survival in CMV Positive Patients Undergoing Haploidentical Hematopoietic Stem Cell Transplantation - Grosso, Dolores; Leiby, Benjamin; Carabasi, Matthew; Filicko-O'Hara, Joanne; Gaballa, Sameh; O'Hara, William; Wagner, John L.; Flomenberg, Neal (Frontiers in Oncology, 2019)
Specific major histocompatibility (MHC) class I alleles dominate anti-CMV responses in a hierarchal manner. These CMV immunodominant (IMD) alleles are associated with a higher magnitude and frequency of cytotoxic lymphocyte responses as compared to other human leukocyte antigen (HLA) alleles. CMV reactivation has been associated with an increased incidence of graft-vs.-host disease and non-relapse mortality, as well as protection from relapse in HLA-matched HSCT settings. Less is known about the impact of CMV reactivation on these major outcomes after haploidentical (HI) HSCT, an increasingly applied therapeutic option. In HI HSCT, the efficiency of the immune response is decreased due to the immune suppression required to cross the MHC barrier as well as MHC mismatch between presenting and responding cells. We hypothesized that the presence of a CMV IMD allele would increase the efficiency of CMV responses after HI HSCT potentially impacting CMV-related outcomes. In this retrospective, multivariable review of 216 HI HSCT patients, we found that CMV+ recipients possessing at least 1 of 5 identified CMV IMD alleles had a lower hazard of death (HR = 0.40, p = 0.003) compared to CMV+ recipients not possessing a CMV IMD allele, and an overall survival rate similar to their CMV– counterparts. The analysis delineated subgroups within the CMV+ population at greater risk for death due to CMV reactivation.